A Economia Política Da Financeirização E Da Crise Do Subprime: Um Estudo Histórico E Das Teorias - Matos, Wallas Gomes De [UNIFESP] (2018)
This Study Aims To Summarize The Main Debates About Financialization And The Crisis That Come Alive In The Fervor And Soon After The Subprime Crisis. The Center Of The Capitalist System Has Been / Is Being Shaken By A Major Crisis - The Bursting Of The Real Estate Bubble In The United States - That Creeps In Time And Space To Beyond Us Borders. This, Therefore, Led To An Important Debate In Different Currents Of Economic Thought. Soon, This Work Comes Ten Years After The Outbreak Of The Crisis In Order To Make An Exposition Of The Main Theories That Make Up The Debate. To Do So, It Begins With An Exposition About The Historical Process That Gave Life To Financialization Culminating In The Crisis Of 2008 And Then To Show The More General Points Of The Main Currents That Seek To Understand This Phenomenon. So Soon, This Dissertation Presents Itself As An Essay On Different Approaches Regarding The Process Of Financialization And The Crisis